The relationship between emotional intelligence and tranformational leadership among employees at Lipis District Council, Kuala Lipis, Pahang / Wan Nur Syazana Zakaria - Zakaria, Wan Nur Syazana (Faculty of Business and Management, 2020)
The purpose of this study is to identify the relationship between emotional intelligence and transformational leadership in the Lipis District Council. This study is to determine the relationship between emotional intelligence and transformational leadership among employees. The questionnaires had been distributed to the employees in the Lipis District Council. The questionnaire is divided into few questions. The questionnaire is a combination of the closed ended question with optional answer by using five-point Likert Scale item: 1 = Strongly Disagree (SD), 2 = Disagree (D), 3 = Neutral (N), 4 = Agree (A), 5 = Strongly Agree (SA). A total of 15 respondents from the total of 137 population was selected for a pilot test. 103 respondents were selected using Convenient Sampling Technique from the remaining 122 respondents. After collecting the questionnaire from the respondents, the data was analysed using Statistical Packages for the Social Sciences (SPSS) version 23. Based on the findings, there is a relationship between emotional intelligence and transformational leadership among employees in the Lipis District Council. The researcher suggested a few recommendations that could be used by the organization and for future research.